Functional equation of characteristic elements of abelian varieties over function fields (ℓ ≠ p) - Pal, Aprameyo (International journal of number theory, 2014)
In this paper we apply methods from the number field case of Perrin-Riou [20] and Zábrádi [32] in the function field setup. In ℤℓ- and GL2-cases (ℓ ≠ p), we prove algebraic functional equations of the Pontryagin dual of Selmer group which give further evidence of the main conjectures of Iwasawa theory. We also prove some parity conjectures in commutative and non-commutative cases. As a consequence, we also get results on the growth behavior of Selmer groups in commutative and non-commutative extension of function fields.
Gesehen am 07.09.2020
First published: 2 December 2013